KONSTRUKSI ISLAM DALAM KEKUASAAN NEGARA - Nurul Aini Musyarofah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2012)
The relationship between Islam and state raises a controversy that includes two main groups;formalists and substantialists. Both of them intend to achieve a good social condition which is inaccordance with Islamic politics. The ideal form of good society to be achieved is principallydescribed in the main source of Islamic law, Al Qur’an and As Sunnah, as follows. A form of goodsociety should supprot equality and justice, egalitarianism, and democracy in its social community.The next problem is what the needed methods and instruments to achieve the ideal Islamic politicsare. In this case, the debate on the formalization and substance of Islamic teaching is related to therunning formal political institution.Each group claims itself to be the most representative to the ideal Islam that often leads to anescalating conflict. On the other hand thr arguments of both groups does not reach the wholeMuslims. As a result, the discourse of Islam and state seems to be elitist and political. As a result,Both groups suspect each other each other and try to utilize the controversy on the relationshipbetween Islam and state to get their own benefit which has no relation with the actualization ofIslamic teaching.